Performance of multiple-source single-relay ultra-wideband networks based on space-time focusing transmission - Ya-fei TIAN; Chen-yang YANG (Tongxin xuebao)
Space-time focusing transmission can reduce multi user interference in ultra-wideband (UWB) communications.Thus enable one relay forwarding the data from multiple sources to multiple destinations.Performance of relay networks with space-time focusing transmission was studied.The outage probabilities in multiple-access phase and broadcasting phase were derived,respectively.The explicit connection between the network throughput and the user number,distance between nodes,UWB pulse width,signal frame duration,and the received signal-to-interferenceand-noise ratio was obtained.By maximizing the network throughput and ana zing the optimization results,some design guidelines for the transmission scheme were provided.The outage probabilities in the two phases were verified through simulations under different path loss factors.